New quill mites (Cheyletoidea: Syringophilidae) parasitizing the black-headed paradise-flycatcher Terpsiphone rufiventer (Passeriformes: Monarchidae) in Gabon - Glowska, Eliza; Schmidt, Brian K. (Zootaxa, 2014)
A new genus of quill mites (Cheyletoidea: Syringophilidae) and two new species Pipicobia terpsiphoni gen. nov. and sp. nov. and Syringophiloidus furthi sp. nov. parasitizing the black-headed paradise-flycatcher Terpsiphone rufiventer (Swainson) (Passeriformes: Monarchidae) in Gabon are described. Three species of the Neopicobia Skoracki, 2011 are moved to the newly established genus: Pipicobia locustella (Skoracki, Bochkov and Wauthy, 2004) comb. nov., Pipicobia pyrrholaemus (Skoracki and Glowska, 2008) comb.nov., and Pipicobia glossopsitta (Skoracki, Glowska and Sikora, 2008) comb.nov. Syringophilids are recorded on hosts of the family Monarchidae and in Gabon for the first time. A key to the genera of the subfamily Picobiinae is proposed.